PEMERIKSAAN FARMAKOGNOSTIK DAN PROFIL KROMATOGRAFI LAPIS TIPIS TUMBUHAN SARANG SEMUT (Myrmeco diapendans Merr. & Perry) ASAL KABUPATEN TELUK BINTUNI PAPUA BARAT - Abd Kadir; Ahmad Najib; Fazlur Rachman (Fakultas Farmasi UMI, 2012)
Pharmacognostic assay and Profile of Thin Layer Chromatography Myrmecodia Plant (Myrmecodia pendens Merr & Perry) from Bintuni Bay, west Papua. Morphologycal Identification showed that Myrmecodia Plant (Myrmecodia pendens Merr & Perry) include magnoliopsida class with steep root system. Leaf anantomy from the leaf showed that anomositic type stomata.Powder extracbility of Myrmecodia Plant (Myrmecodia pendens Merr & Perry) including total ash is 33,92% and insoluble acid ash is 7,78%. While in the water soluble extractive 15,09% and aethanol soluble extractive 5,40%. Chemical identification on the tuberous powder showed that it is consist of tannin (pirogalotanin) and flavanoid. Profile of Thin layer chromatography obtained total spot more diethyl ether extract equel to 8 spot and n-butanol extract equal to 5 spot with n-hexene : ethyl acetate (8:2( and Chloroform : methanol : water (10:6:0,5).Key words : Pharmacognostic, Myrmecodia pendens, Thin layer chromatography